Kinetics study of hydrogen adsorption over Pt/MoO3 - Triwahyono, Sugeng; Abdul Jalil, Aishah; Timmiati, Sharifah Najiha; Ruslan, Nurun Najwa; Hattori, Hideshi (Elsevier, 2010)
The rate controlling step and the energy barrier involved in the hydrogen adsorption over Pt/MoO3 were studied. Rates of hydrogen adsorption on Pt/MoO3 were measured at the adsorption temperature range of 323–573 K and at the initial hydrogen pressure of 6.7 kPa. The rate of hydrogen uptake was very high for the initial few minutes for adsorption at and above 473 K, and reached equilibrium within 2 h. At and below 423 K, the hydrogen uptake still continued and did not reach equilibrium after 10 h. The hydrogen uptake exceeded the H/Pt ratio of unity for adsorption at and above 423 K, indicating that hydrogen adsorption involves hydrogen atom spillover and surface diffusion of the spiltover hydrogen atom over the bulk surface of MoO3 followed by formation of HxMoO3. The hydrogen uptake was scarcely appreciable for Pt-free MoO3. The rate controlling step of the hydrogen adsorption on Pt/MoO3 was the surface diffusion of the spiltover hydrogen with the activation energy of 83.1 kJ/mol. The isosteric heats of hydrogen adsorption on Pt/MoO3 were 18.1–16.9 kJ/mol for the hydrogen uptake range 2.4–2.8 × 1019 H-atom/g-cat. Similarities and differences in hydrogen adsorption on Pt/SO42-–ZrO2, Pt/WO3–ZrO2 and Pt/MoO3 catalysts are discussed.